Husserl's Concept of Position-taking and Second Nature - Alejandro Arango (Rosenberg & Sellier, 2016)
I argue that Husserl’s concept of position-taking, Stellungnahme, is adequate to understand the idea of second nature as an issue of philosophical anthropology. I claim that the methodological focus must be the living subject that acts and lives among others, and that the notion of second nature must respond to precisely this fundamental active character of subjectivity. The appropriate concept should satisfy two additional desiderata. First, it should be able to develop alongside the biological, psychological, and social individual development. Second, it should be able to underlie the vast diversity of human beings within and across communities. As possible candidates, I contrast position-taking with two types of habit-like concepts: instinct and habitus, on the one hand, and customary habits, on the other. I argue that position-taking represents the active aspect of the subject while the habit-like concepts are passive. A subject’s position-takings and ensuing comportments are tied together by motivations, which evince a certain consistency, and for this reason are expression of the subject’s identity. I conclude by nuancing the relation between Stellungnahme and passivity. Passivity is deemed necessary to action but subservient to it; position-taking is thought to be prior to passivity.